Formulation and Characterization of Myricetin Solid Lipid Nanoparticles (SLNs) via Ultrasonication Method - Dewi Zulfa Rosida; Muhammad Dzakwan; Hery Muhamad Ansory (Griya Eka Sejahtera, 2026)
Background: Myricetin is a flavonol flavonoid with promising neuroprotective and antioxidant activities. However, its therapeutic application is severely limited by poor water solubility and a low dissolution rate. This study aimed to enhance the solubility and formulation stability of myricetin by developing a Solid Lipid Nanoparticle (SLN) delivery system.Methods: Myricetin-SLNs were prepared via the ultrasonication method using Tween 80 as a nonionic surfactant. Lipid screening was conducted using Imwitor 491, Dynasan 118, and Apifil at concentrations of 2%, 4%, and 6%. The selected lipid (Apifil at 2%, 3%, 4%, and 5%) was melted at 100 °C, homogenized with the aqueous phase using a magnetic stirrer at 2000 rpm for 1 hour, cooled to 35 °C, and subjected to probe ultrasonication at 35 kHz for 5 minutes. The SLNs were characterized using a particle size analyzer and a UV-Vis spectrophotometer to evaluate storage stability, particle size, polydispersity index (PDI), entrapment efficiency, zeta potential, and DPPH free radical scavenging activity.Results: Lipid screening revealed that Apifil-based formulations provided superior physical stability compared to Imwitor 491 and Dynasan 118. The optimized formulation, F7 (containing 2% Apifil), yielded the smallest particle size of 105.5±0.70 nm, a highly homogeneous PDI of 0.232, a zeta potential of -20.52 mV, and the highest entrapment efficiency at 73.56%. Furthermore, F7 demonstrated strong antioxidant activity with an IC50 value of 38.77 ppm, compared to pure myricetin (14.44 ppm).Conclusion: The formulation of myricetin into Solid Lipid Nanoparticles using 2% Apifil via ultrasonication effectively minimizes particle size and maximizes entrapment efficiency. Although it exhibits lower long-term storage stability at room temperature, it successfully preserves potent antioxidant activity, offering a promising approach for health sciences and advanced drug delivery applications